Meningkatkan Kemampuan Membaca Cepat melalui Teknik Skimming di MI Tahfidz Jalaluddin Arrumi Jember - Rohmah, Siti; Jamilah, Siti Sarohan; Ulum, Soniful (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ speed reading ability through the implementation of skimming techniques at MI Tahfidz Jalaluddin Arrumi Jember. The method used is Classroom Action Research (CAR), consisting of two cycles with the stages of planning, implementation, observation, and reflection. The research subjects were fifth-grade students who faced difficulties in speed reading and effectively comprehending texts. Data were collected through reading speed tests, observation sheets, and interviews with teachers and students. The results showed that the systematic application of skimming techniques could enhance students’ speed reading skills. In the first cycle, students struggled to identify the main ideas and extract key information from the text. However, in the second cycle, there was a significant improvement in both reading speed and comprehension. The key factors contributing to this success included the use of reading materials appropriate for the students’ developmental level, regular practice in applying skimming techniques, and teacher guidance in teaching effective reading strategies. Thus, skimming techniques can serve as an effective alternative in improving students’ speed reading skills in elementary schools, especially for those who still experience difficulties in quickly comprehending reading materials.